1983
DOI: 10.1111/j.1464-410x.1983.tb03423.x
|View full text |Cite
|
Sign up to set email alerts
|

Semen Analysis in Testicular Cancer and Hodgkin's Disease: Pre‐ and Post‐Treatment Findings and Implications for Cryopreservation

Abstract: Over a 7-year period, seminal analysis has been performed on 208 patients with testicular tumours, after orchiectomy, but before any other treatment. Only 22% of 54 patients with seminomas, and 29% of 154 patients with teratomas or mixed tumours, had sperm counts exceeding 10 million per ml. Very low sperm counts were observed in some patients who had previously fathered children. Post-treatment sperm counts were done in 117 patients, 80 of whom had received multiple drug chemotherapy: 42 of these men had pre-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
40
0
5

Year Published

1987
1987
2008
2008

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 153 publications
(46 citation statements)
references
References 14 publications
1
40
0
5
Order By: Relevance
“…Since most patients with testicular cancer are of a young age, the impact of therapy on sexual function and fertility has become increasingly important. Testicular cancer patients may have a reduced spermatogenesis ('hypospermia') at diagnosis (Hendry et al, 1983;Berthelsen and Skakkebaek, 1984;Cassileth and Steinfeld, 1987;Moynihan, 1987;Nijman et al, 1987;Fossa et al, 1988;Sleijfer et al, 1995) and after orchidectomy (Lampe et al, 1997), and only between 22 and 63% of patients fulfil the definition of normospermia at diagnosis (Hendry et al, 1983;Fossa et al, 1985;Nijman et al, 1987;Lampe et al, 1997). Three disease-associated conditions, local structural abnormalities detected by biopsy of the contralateral testis, the presence of sperm antibodies and endocrine factors, may be responsible (Berthelsen and Skakkebaek, 1984;Guazzieri et al, 1985).…”
mentioning
confidence: 99%
“…Since most patients with testicular cancer are of a young age, the impact of therapy on sexual function and fertility has become increasingly important. Testicular cancer patients may have a reduced spermatogenesis ('hypospermia') at diagnosis (Hendry et al, 1983;Berthelsen and Skakkebaek, 1984;Cassileth and Steinfeld, 1987;Moynihan, 1987;Nijman et al, 1987;Fossa et al, 1988;Sleijfer et al, 1995) and after orchidectomy (Lampe et al, 1997), and only between 22 and 63% of patients fulfil the definition of normospermia at diagnosis (Hendry et al, 1983;Fossa et al, 1985;Nijman et al, 1987;Lampe et al, 1997). Three disease-associated conditions, local structural abnormalities detected by biopsy of the contralateral testis, the presence of sperm antibodies and endocrine factors, may be responsible (Berthelsen and Skakkebaek, 1984;Guazzieri et al, 1985).…”
mentioning
confidence: 99%
“…De nombreux auteurs ont constat6 que le sperme des jeunes canc6reux 6tait souvent alt6r6 [10,8,18,1].…”
Section: Caracteristiques Initiales Du Spermeunclassified
“…L'atteinte initiale du sperme est nettement plus importante dans le cancer du testicule que dans la maladie de Hodgkin [10].…”
Section: Caracteristiques Initiales Du Spermeunclassified
“…Some schedules for advanced germ cell tumours may also cause infertility. Previous studies (Hendry et al, 1983) have demonstrated that insemination with semen cryopreserved before the start of chemotherapy may result in successful pregnancy. Unfortunately many of these patients present with low sperm counts or poorly motile sperm before treatment starts (Sanger et al, 1980).…”
mentioning
confidence: 99%
“…Despite these limitations a number of centres in the UK offer semen cryopreservation for cancer patients. Although a single centre has published its results (Hendry et al, 1983;Scammell et al, 1985) the practice throughout the UK has not been reviewed. We set out to examine the availability of this service throughout the country and to assess its success.…”
mentioning
confidence: 99%